Restorative treatment decisions for carious lesions: Do Russian dentists and dental students apply minimal intervention dentistry? - Sergei N. Drachev; Alexandra S. Galieva; Tatiana N. Yushmanova; Elena A. Polivanaya; Lina Stangvaltaite-Mouhat; Rania Al-Mahdi; Jukka Leinonen; Linda Maria Stein; Nadezhda G. Davidova; Mohammed Al-Haroni (BMC, 2021)
Abstract Background The concept of minimal intervention dentistry (MID) includes both delayed restorative treatment and conservative caries removal, and is now recognised as an evidence-based approach for dental caries management. In order to determine if dental professionals in Russia are incorporating this concept into their clinical practice, we investigated the restorative treatment decisions of Russian dentists and dental students, and the factors associated with these decisions. Methods We included 171 general dental practitioners and dental therapists (collectively referred to here as "dentists") from North-West Russia, and 76 dental undergraduate students from the Northern State Medical University in Arkhangelsk (response rate of 11.5% and 67.9%, respectively). Participants completed a questionnaire, which collected background information (sex, region of work, place of dental school graduation, practice type, years of working experience, working in an urban or rural area, and specialisation in restorative dentistry) and information on restorative treatment decisions for proximal and occlusal carious lesions of permanent teeth. Treatment options in accordance with MID were defined as intervention at dentin level and minimally invasive cavity preparation. Multinomial logistic regression was used for statistical analysis. Results For the proximal carious lesion, 9.4% of participants said they would employ both MID treatment options; 60.7% said they would choose only one; and 29.9% said they would use neither option. For the occlusal carious lesion, the corresponding figures were 37.2%, 52.1%, and 10.7%. No differences in restorative treatment options were observed among general dental practitioners, dental therapists, and dental students. For the proximal carious lesion, dentists from regions outside Arkhangelsk had 4.15 (95% confidence interval [CI] 1.13-15.27) times higher odds of following one versus both MID treatment options. For the occlusal carious lesion, working experience above 15 years was associated with higher odds of using only one versus both MID treatment options (adjusted odds ratio = 3.04, 95% CI 1.33-6.91). Almost all respondents preferred tooth-coloured materials for restorations; more than 75% chose resin-based composite. Conclusions The majority of Russian dentists and dental students do not apply the MID concept when treating dental caries in permanent teeth. Clinical protocols on dental caries treatment and dental school curriculums should be updated to place an enhanced focus on evidence-based practice and preventive strategies. Further studies with larger samples of Russian dentists and dental students and alternative methods of recruitment are needed to validate our results.